Compendium for the antenatal care of high-risk pregnancies - Narayan, Harini (Oxford : Oxford University Press, 2015)
High-risk pregnancies are increasing and form a significant proportion of the pregnant patient population. This book is designed to provide a practical and accessible individualised framework of information for doctors in busy clinical environments, and to integrate the specialist care offered to women with high-risk pregnancies. For each condition, the book covers vital points on risk reduction, clinical governance, discussion with patients, and required documentation.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Pregnancy -- Complications